THE REALITY OF AGRICULTURAL TECHNIQUES USED BY FARMERS TO REDUCE LOSSES IN WHEAT AND BARLEY CROPS IN THE GOVERNORATES OF THE CENTRAL REGION OF IRAQ - & Al badry, Shaheed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this research to investigate  the agricultural techniques used by farmers in reducing the losses of wheat and barley crops in the governorates of the central of Iraq. To achieve the research objectives, use descriptive approach, which is one of the research methods The eight governorates of the central region of Iraq were selected except of Salah al-Din and Anbar were excluded due to poor security conditions. Random sampleS of 50% were selected from three governorates covered (Najaf, Karbala, Babylon) with33, agricultural divisions (25%) and 8, agricultural divisions distributed over the governorates were covered by the research. A random sample of 1% of the wheat and barley farmers were selected in the agricultural population covered by the research and 152, farmers. In order to obtain the information, a questionnaire was prepared for this purpose, which included 38, paragraphs distributed over 8, axes. The results revealed a decrease in the level of knowledge among farmers in the quantities of losses before and during the harvest, and the lack of numbers of harvesters and their distribution is incorrect, most of them of the old type, and the low knowledge of farmers the importance of harvesting organizations. It cam be recommends the use of modern agricultural techniques and increases the numbers, productable for cultivate areas.